P0126RENAL TRANSPLANT PATIENTS UNDER CALCINEURIN INHIBITOR THERAPY RAPIDLY ACQUIRE AN ABERRANT LYSOSOMAL LESION IN PROXIMAL TUBULAR CELLS. (6th June 2020) - Vervaet, Benjamin; Kojc, Nika; Nast, Cynthia; Schreurs, Gerd; D'Haese, Patrick; De Broe, Marc
Abstract: Background and Aims: Calcineurin inhibitor therapy has changed the field of (renal) transplantation by considerably prolonging graft survival. Yet, all immunosuppressive calcineurin inhibitors are nephrotoxic that eventually contribute to complete scarring of the renal allograft. In renal biopsy analysis many histopathological features have been considered indicative of CNI nephrotoxicity, i.e. striped fibrosis, vascular hyalinosis, isometric tubular vacuolization, glomerulosclerosis, cellular infiltration and tubular atrophy, however, all are rather aspecific and can be secondary to many other causes. During the course of evaluating the specificity of a recently discovered proximal epithelial lysosomal lesion (i.e. multiple enlarged (>1, 2µm) dysmorphic lysosomes containing dispersed electron dense non-membrane bound aggregates) in patients with Chronic Interstitial Nephropathy in Agricultural Communities (CINAC), we observed it to be present in renal transplant patients treated with cyclosporine or tacrolimus. Here, we test the hypothesis whether this lysosomal lesion is acquired during CNI therapy. Method: A retrospective transmission electron microscopic analysis was performed to evaluate the presence of the typical lysosomal lesion on the following biopsies from renal transplant patients: 20 deceased donor implantation biopsies; 5 living donor implantation biopsies. For another 10 additional deceased donor renal allograft recipients, we evaluated implantation as well as protocol biopsies taken after 6 and 12 months of CNI treatment that started immediately after transplantation. Also included were 24 indication biopsies of CNI treated renal transplants. Results: Of the total set of implantation biopsies (n=35), 2 (6%) were positive for the aberrant lysosomal phenotype on EM, whereas in the protocol and indication biopsies prevalence of the lesion was considerably higher ranging between 56% (protocol) and 80% (indication) of cases. Conclusion: CNI therapy is associated with the fairly rapid appearance of a particular proximal tubular lysosomal phenotype observable on EM, that was not (or rarely) present at implantation. Whether this lesion is related to CNI toxicity and indicative for the outcome for the graft and/or patient survival after renal transplantation has to be investigated in a prospective trial.